Physical mechanisms and parameters for models of microstructure evolution under irradiation in Fe alloys – Part I: Pure Fe. (December 2021) - Malerba, L.; Anento, N.; Balbuena, J.P.; Becquart, C.S.; Castin, N.; Caturla, M.J.; Domain, C.; Guerrero, C.; Ortiz, C.J.; Pannier, B.; Serra, A.
Highlights: Physical mechanisms and relevant parameters that govern microstructure evolution in α-Fe under irradiation are reviewed. Literature results are discussed in a consistent framework along with new results. A set of recommended parameters and educated guess approximations are put forward. Remaining knowledge gaps are clearly identified. Abstract: This paper is the first of three that overview the main mechanisms that drive the microstructure evolution in Fe alloys under irradiation. It focuses on pure α-Fe and compiles the parameters that describe quantitatively the mobility and stability of point-defects and especially their clusters, including possible reactions and criteria to decide when they should react. These parameters are the result of several years of calculations and application in microstructure evolution models. They are mainly collected from the literature and the parameter choice tries to reconcile different sets of values that, while being in general qualitatively similar, are often quantitatively not coincident. A few calculation results are presented here for the first time to support specific approximations concerning defect properties or features. Since calculations cannot cover all possible defect configurations, the definition of these parameters often requires educated guesses to fill knowledge gaps. These guesses are here listed and discussed whenever relevant. This is therefore a "hands-on" paper that: (i) collects in a single report most microstructure evolution parameters that are found in the literature for irradiated α-Fe, including a discussion of the most important mechanisms at play based on current knowledge; (ii) selects a ready-to-use set that can be employed in microstructure evolution models, such as those based on object kinetic Monte Carlo (OKMC) methods. This work also identifies parameters that are needed, but not known, hopefully prompting corresponding calculations in the future.